Human Salivary Amylase Gene Copy Number Impacts Oral and Gut Microbiomes - Poole, Angela C.; Goodrich, Julia K.; Youngblut, Nicholas D.; Luque, Guillermo G.; Ruaud, Albane; Sutter, Jessica L.; Waters, Jillian L.; Shi, Qiaojuan; El-Hadidi, Mohamed; Johnson, Lynn M.; Bar, Haim Y.; Huson, Daniel H.; et al. (Cell host & microbe, 2019)
Host genetic variation influences microbiome composition. While studies have focused on associations between the gut microbiome and specific alleles, gene copy number (CN) also varies. We relate microbiome diversity to CN variation of the AMY1 locus, which encodes salivary amylase, facilitating starch digestion. After imputing AMY1-CN for ∼1,000 subjects, we identified taxa differentiating fecal microbiomes of high and low AMY1-CN hosts. In a month-long diet intervention study, we show that diet standardization drove gut microbiome convergence, and AMY1-CN correlated with oral and gut microbiome composition and function. The microbiomes of low-AMY1-CN subjects had enhanced capacity to break down complex carbohydrates. High-AMY1-CN subjects had higher levels of salivary Porphyromonas; their gut microbiota had increased abundance of resistant starch-degrading microbes, produced higher levels of short-chain fatty acids, and drove higher adiposity when transferred to germ-free mice. This study establishes AMY1-CN as a genetic factor associated with microbiome composition and function. [Display omitted] •High AMY1 copy number (CN) is associated with higher levels of Porphyromonas in saliva•High AMY1-CN stool has more resistant starch degraders; drives more adiposity in GF mice•Stool short-chain fatty acid levels are predictive of salivary amylase activity•Upon diet standardization, gut microbiomes converged without eliminating differences Poole et al. examine how copy-number (CN) variation of the AMY1 gene, encoding salivary amylase, relates to human microbiomes. Individuals with high AMY1-CN have an increased number of oral Porphyromonas, which is linked to periodontitis. Their gut microbiotas have a higher abundance of resistant starch-degrading microbes and drive higher adiposity when transferred to germ-free mice.